2013
DOI: 10.1186/1757-2215-6-61
|View full text |Cite
|
Sign up to set email alerts
|

Splice variants of zinc finger protein 695 mRNA associated to ovarian cancer

Abstract: BackgroundStudies of alternative mRNA splicing (AS) in health and disease have yet to yield the complete picture of protein diversity and its role in physiology and pathology. Some forms of cancer appear to be associated to certain alternative mRNA splice variants, but their role in the cancer development and outcome is unclear.MethodsWe examined AS profiles by means of whole genome exon expression microarrays (Affymetrix GeneChip 1.0) in ovarian tumors and ovarian cancer-derived cell lines, compared to health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…The upregulation of the isoforms in malignant tissue seemed to occur simultaneously rather than through a variant switch mechanism. The differential expression of KRAB-ZNF splicing isoforms in cancer was reported only by Juarez-Mendez and colleagues (Juarez-Mendez et al, 2013), who demonstrated a specific increase of ZNF695 variants in ovarian cancer compared to normal cells. Interestingly, we frequently observed increased expression of the variants that are not translated to a protein or are short forms devoid of KRAB or zinc finger domains.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The upregulation of the isoforms in malignant tissue seemed to occur simultaneously rather than through a variant switch mechanism. The differential expression of KRAB-ZNF splicing isoforms in cancer was reported only by Juarez-Mendez and colleagues (Juarez-Mendez et al, 2013), who demonstrated a specific increase of ZNF695 variants in ovarian cancer compared to normal cells. Interestingly, we frequently observed increased expression of the variants that are not translated to a protein or are short forms devoid of KRAB or zinc finger domains.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, their exact molecular functions remain unknown. This includes ZNF695 (Juarez- Mendez et al, 2013;Li et al, 2015Takahashi et al, 2015), ZNF320 (Chernova et al, 2001), ZNF138 (Tommerup and Vissing, 1995), ZNF200 (Peedicayil et al, 2010), ZNF707 (Nesslinger et al, 2007), and ZNF354A (von Eyben, 2004). Interestingly, cancer-related upregulation of ZNF695, ZNF714, and ZNF138 mirrors the differential expression observed between pluripotent stem cells and differentiated cells (Oleksiewicz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This C2H2 is the most characteristic zinc nger so far and is very common in mammal transcription factors [11]. It has been con rmed that different members of zinc nger proteins, such as ZNF608 [12], ZNF695 [13], ZEB1 [14] and Snail [15], are reported to be involved in the development and metastasis of OC, suggesting that zinc nger proteins may play an important role in OC. Compared with the welldocumented zinc nger protein members, the biological function and role of ZNF280A in OC has been poorly reported.…”
Section: Introductionmentioning
confidence: 94%
“…The data were download of ArrayExpress (https://www.ebi.ac.uk/ arrayexpress/) [44] or Gene Expression Omnibus (GEO) (https://www.ncbi.nlm.nih.gov/geo/) [45]. The microarray analysis was performed using Partek Genomics Suite v7.17 according to previous reports [46].…”
Section: Alternative Splicing In the Most Common Cancer Typesmentioning
confidence: 99%